Recent Advances in Biological Active Sulfonamide based Hybrid Compounds Part B: Two-Component Sulfonamide Hybrids - Ghomashi, Shakila; Ghomashi, Reihane; Aghaei, Hamidreza; Massah, Ahmad R. (Current Medicinal Chemistry, 2023)
Sulfonamide compounds, also known as sulfa drugs, are a significant class of synthetic bacteriostatic antimicrobials and were the primary source of therapy against bacterial infections before the introduction of penicillin in 1941. Hybridization of sulfonamides with various pharmaceutically active heterocyclic moieties leads to sulfonamide hybrids with a wide variety of biological activities. Part B of this review presents the most recent advances in designing and developing more two-component sulfonamide hybrids containing triazole, thiadiazole, triazine, oxazole/ benzoxazole, isoxazole, oxadiazole, imidazole, benzimidazole, furan, benzofuran, thiophene, pyrrole, indazole, tetrazole, chromene/ chromone, pyridazine, quinoxaline, acridine, phthalazine, and xanthone between 2015 and 2020. We hope this review helps the scientific community in designing more useful sulfonamide hybrid drugs.
Keywords: hybridization